Butyrate downregulates α2β1 integrin: a possible role in the induction of apoptosis in colorectal cancer cell lines. (1st May 2003) - Buda, A; Qualtrough, D; Jepson, M A; Martines, D; Paraskeva, C; Pignatelli, M
Abstract : Background: Integrins mediate cell matrix adhesion and regulate cell growth and survival. In colonic epithelial cells, α2 β1 integrin controls glandular differentiation and proliferation. Butyrate stimulates differentiation and induces apoptosis in vitro. Aims: We investigated whether butyrate induction of apoptosis was associated with perturbation of integrin mediated cell matrix adhesion. Methods: Three colonic cancer cell lines (SW1222, SW620, LS174T) were studied. Adhesion to extracellular matrix proteins, expression of α2 β1 integrin, and apoptosis were studied in adherent cells after treatment with 4 mM butyrate. Results: Butyrate decreased the attachment to type I collagen in SW620 cells and type I and IV collagen in LS174T cells. The decreased cell attachment was associated with downregulation of α2 β1 integrin and increased apoptosis in adherent cells. No changes in α2 β1 expression or matrix adhesion were seen in SW1222 cells, which were also found to be less sensitive to butyrate induction of apoptosis. Downregulation of α2 β1 integrin preceded the detection of apoptosis. Conclusion: Apoptosis induced by butyrate is associated with downregulation of expression and functional activity of α2 β1 integrin. Perturbation of cell matrix adhesion may be a novel mechanism by which butyrate induces apoptosis in colorectal cancer cells.